New data on numbers and distribution of birds of prey breeding in Belarus - Dombrovski, Valery Cheslavovich; Ivanovski, Vladimir Valentinovich (2005)
During 1998-2002, all species of diurnal raptors were counted in Belarus. The method used was observation of a study area with the help of optics from a series of points and subsequent mapping of the hunting and presumed nesting ranges of birds of prey. The total area surveyed was about 9,000 km². Estimated quantity of the species: Honey Buzzard - 8,000-11,000 pairs; Black Kite - 200-230; Red Kite - 3-10; White-tailed Eagle - 85-105; Short-toed Eagle - 530-700; Marsh Harrier - 6,000-9,000; Hen Harrier - 600-800; Montagu's Harrier - 3,000-5,000; Goshawk - 3,500-5,000; Sparrowhawk - 6,500- 8,500; Common Buzzard - 18,000-24,000; Lesser Spotted Eagle - 3,200-3,800; Greater Spotted Eagle - 150-200; Golden Eagle - 25-35; Booted Eagle - 10-15; Osprey - 150-180 pairs; Common Kestrel - 1,200-1,700; Red-footed Falcon - 10-30; Merlin - 300-350; Hobby - 2,500-2,700; Peregrine - 0-3 pairs.